PENGARUH KOMPOSISI DAN KUAT TEKAN TERHADAP TINGKAT KERAPUHAN BRIKET ARANG BIOMASA CAMPUR BATUBARA DENGAN TEPUNG KANJI SEBAGAI PEREKAT - Dailami Dailami; Pribadyo Pribadyo; Hanif Hanif (VOCATECH: Vocational Education and Technology Journal, 2020)
Abstract West Aceh is one of the regions in Aceh Province that has natural resources in the form of coal mines and biomass in the form of rice husks, sawdust, peanut shells and coconut shells which have not been utilized. One of the efforts to exploit this potential is by processing it into bioarang coal briquettes into alternative fuels through the briquette process. The purpose of this study was to determine the level of brittleness in the manufacture of coal and biomass briquettes. The research was conducted by varying the mass composition of the mass weight of the mixture between coal and sawdust biomass, rice husks, coconut shell and peanut shells by 50%, 60%, 70% for coal and 40%, 30%, and 20% for biomass. The adhesive (glue) in the form of starch is 10%. Pressure applied is 80 lb/in2, 100 lb/in2 and 120 lb/in2. The test used the drop test method with the calculation procedure using the ASTM D 440-86 r02 standard. The results showed that the ratio of the composition of the mixture of raw materials and pressing pressure had an effect on the brittleness of the briquettes. The highest brittleness was obtained at a composition ratio of 50% coal: 40% coconut shell: 10% starch at a pressure of 80 lb/in2 obtained a weight of 24, 24 grams. The lowest brittleness is obtained at a mixture composition of 60% coal: 30% peanut shell: 10% starch at a pressure of 80 lb/in2, the weight is 29.7 grams. Keyword Coal, biomass, starch, hydraulic pressure. __________________________ Abstrak: Aceh Barat merupakan salah satu wilayah di Provinsi Aceh yang memiliki sumber daya alam berupa tambang batu bara serta biomassa berupa sekam padi, serbuk kayu, kulit kacang tanah serta tempurung kelapa yang belum termanfaatkan. Salah satu upaya untuk memanfaatkan potensi tersebut adalah dengan cara diolah menjadi briket bioarang batu bara menjadi bahan bakar alternatif melalui proses pembriketan. Tujuan dari penelitian untuk mengetahui tingkat kerapuhan pada pembuatan briket campuran batubara dan biomasa. Penelitian dilakukan dengan memvariasikan komposisi berat masa campuran antara batu bara dan biomasa serbuk kayu, sekam padi, tempurung kelapa dan kulit kacang tanah sebesar 50%, 60%, 70% untuk batubara dan 40%, 30%, dan 20% untuk biomasa. Bahan perekat (lem) berupa tepung kanji sebesar 10%. Tekanan diberikan sebesar 80 lb/in2, 100 lb/in2 dan 120 lb/in2. Pengujian menggunakan metode drop test dengan prosedur perhitungan menggunakan standar ASTM D 440-86 r02. Dari hasil penelitian menunjukkan bahwa perbandingan komposisi campuran bahan baku dan tekanan pengepresan berpengaruh terhadap tingkat kerapuhan briket. Kerapuhan tertinggi diperoleh pada perbandingan komposisi sebesar 50% batu bara: 40% tempurung kelapa: 10% tepung kanji pada tekanan 80 lb/in2 diperoleh berat 24, 24gram. Kerapuhan terendah diperoleh pada perbandingan komposisi campuran 60% batu bara: 30% kulit kacang tanah:10% tepung kanji pada tekanan 80 lb/in2 diperoleh berat 29, 7gram. Kata kunci Batu bara, biomassa, tepung kanji, tekanan hidraulik __________________________